A hyperbranched copolymer and its preparation method and application

By introducing hyperbranched copolymers into the anion exchange membrane, using superacid catalytic polymerization and quaternization reactions, the problems of low conductivity of anion exchange membrane and difficulty in preparing ultra-thin films are solved, and high mechanical strength and high conductivity are achieved Anion exchange membrane, suitable for efficient applications of fuel cells.

CN115947933BActive Publication Date: 2025-02-07CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310107139.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2025-02-07
Estimated Expiration
2043-02-13

AI Technical Summary

Technical Problem

The existing anion exchange membrane has a low conductivity and it is difficult to prepare ultra-thin unsupported anion exchange membrane, which limits its application in fuel cells.

Method used

A hyperbranched copolymer was developed to prepare anion exchange membrane with high mechanical strength and adjustable thickness through superacid catalytic polymerization and quaternization reaction. The copolymer contains branched monomers and a long alkyl chain structure, which can improve the degree of phase separation and ionic conductivity of the film.

Benefits of technology

Anion exchange membrane with adjustable thickness to 8 microns is achieved without support, which improves the mechanical strength and conductivity of the membrane and is suitable for efficient fuel cell applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004075557500000021
    Figure BDA0004075557500000021
  • Figure BDA0004075557500000022
    Figure BDA0004075557500000022
  • Figure BDA0004075557500000041
    Figure BDA0004075557500000041
Patent Text Reader

Abstract

The present invention provides a hyperbranched copolymer, comprising a structural unit shown in formula (1). The present invention provides a novel branched monomer, and introduces it to prepare a hyperbranched polymethylpiperidine-terphenyl polymer without an ether bond through a superacid catalytic polymerization reaction, and then prepares a cyclic quaternary ammonium type anion exchange membrane through a quaternization reaction. The branched monomer prepared by the present invention has the structural characteristics of a long alkyl chain, which can effectively improve the phase separation degree of the membrane and improve the ionic conductivity; at the same time, due to its high reactivity and flexibility, the obtained membrane has high mechanical strength, and the thickness of the membrane can be regulated to 8 microns (without support).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copolymers, and in particular relates to a hyperbranched copolymer and a preparation method and application thereof. Background Art

[0002] Anion exchange membrane fuel cells (AEMFCs) work in an alkaline environment and have significant characteristics such as low use of precious metals such as platinum and ruthenium and low fuel permeability, which have attracted widespread attention. However, due to the low ion mobility of hydroxide ions (about 57% of hydrogen ions), the conductivity of anion exchange membranes is lower than that of proton membranes under the same conditions, which limits the widespread application of anion membranes. In order to improve the conductivity and battery power density of anion exchange membranes, a lower membrane thickness is indispensable because it can effectively reduce the surface resistance of the membrane electrode. The prior art obtains a composite anion exchange membrane with a mechanical strength of 80MPa and a membrane thickness of 10 microns by using high-density polyethylene as a substrate enhancement strategy. A self-supporting anion exchange membrane with a thickness of 10 microns was prepared by introducing quaternary biphenyl as a comonomer. By reducing the membrane thickness, the mass transfer and comprehensive performance of electrochemical devices are improved. However, it is extremely challenging to be able to directly prepare ultra-thin (less than 10 microns) unsupported anion exchange membranes. Therefore, the development of anion exchange membranes with ultra-thin thickness is of great significance not only for improving the device level and expanding the application field of anion exchange membranes, but also for promoting the promotion of alkali-resistant materials. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a hyperbranched copolymer and a preparation method and application thereof. The film prepared from the hyperbranched copolymer provided by the present invention has good mechanical properties and a thin film thickness, and a thin film thickness is obtained under unsupported conditions.

[0004] The present invention provides a hyperbranched copolymer, comprising a structural unit represented by formula (1):

[0005]

[0006] In formula (1), 0<x≤0.1, 0≤n≤14.

[0007] The present invention provides a method for preparing a hyperbranched copolymer, comprising:

[0008] Under the action of a catalyst, the compound of formula (2), the compound of formula (3) and the compound of formula (4) are reacted in a solvent to obtain a polymer including a structural unit of formula (5);

[0009] The polymer and methyl iodide are subjected to a quaternization reaction in a polar solvent to obtain a polymer comprising a structural unit of formula (1);

[0010]

[0011] In formula (3), 0≤n≤14,

[0012] The terminal group in formula (4) is a methyl group;

[0013] In formula (5), 0<x≤0.1, 0≤n≤14.

[0014] Preferably, the catalyst is an acidic catalyst selected from one or more of trifluoromethanesulfonic acid, methanesulfonic acid and Eaton's reagent.

[0015] Preferably, the catalyst is added under low temperature conditions, and the low temperature is -40 to 10°C.

[0016] Preferably, the molar ratio of the compound of formula (2), the compound of formula (4) and the compound of formula (3) is (0.9-1.0):(1.0-1.1):(0-0.1).

[0017] Preferably, the solvent is an aprotic solvent selected from one or more of dichloromethane and chloroform.

[0018] Preferably, the volume ratio of the catalyst to the solvent is 1:(1.0-2.0).

[0019] Preferably, the polar solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.

[0020] Preferably, the temperature of the reaction and the quaternization reaction is independently selected from room temperature;

[0021] The reaction time is 2 to 6 hours;

[0022] The quaternization reaction time is 20 to 30 hours.

[0023] The present invention provides a film, which is prepared from the hyperbranched copolymer described in the above technical solution or the hyperbranched copolymer prepared by the method described in the above technical solution.

[0024] Although many types of anion exchange membrane materials have been developed, the conductivity of anion exchange membranes is low due to the low ion mobility of hydroxide ions. At the same time, based on the structural characteristics of the polymer main chain, the thickness of the prepared membrane is generally more than 20 microns to meet the strength requirements during use, resulting in higher surface resistance in fuel cell applications.

[0025] The present invention provides a new type of branched monomer, and introduces it through superacid catalytic polymerization to prepare a hyperbranched polymethylpiperidine-terphenyl polymer without ether bonds, and then prepares a cyclic quaternary ammonium type anion exchange membrane through a quaternization reaction. The branched monomer prepared by the present invention has the structural characteristics of a long alkyl chain, which can effectively improve the phase separation degree of the membrane and improve the ion conductivity; at the same time, due to its high reactivity and flexibility, the obtained membrane has high mechanical strength, and the thickness of the membrane can be controlled to 8 microns. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 SAXS graph and mechanical properties graph of the polyelectrolyte membrane prepared in the embodiment of the present invention;

[0027] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of the product prepared in Example 1 of the present invention;

[0028] Figure 3 This is a picture of the product prepared in Example 3 of the present invention;

[0029] Figure 4 This is a picture of the product prepared in Example 2 of the present invention;

[0030] Figure 5 This is a picture of the product prepared in Example 1 of the present invention;

[0031] Figure 6 This is the nuclear magnetic resonance spectrum of the dodecylfluorene monomer prepared in Example 6 of the present invention;

[0032] Figure 7 This is the nuclear magnetic resonance spectrum of the hexylfluorene monomer prepared in Example 6 of the present invention;

[0033] Figure 8 This is the nuclear magnetic resonance spectrum of the ethylfluorene monomer prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The present invention provides a hyperbranched copolymer, comprising a structural unit represented by formula (1):

[0036]

[0037] In formula (1), 0<x≤0.1, 0≤n≤14.

[0038] In the present invention, the x is preferably 0.01-0.08, more preferably 0.01-0.05, more preferably 0.02-0.04, and most preferably 0.03; the n is preferably 0-12, more preferably 4-10, more preferably 8-10, and most preferably 10.

[0039] The present invention provides a method for preparing a hyperbranched copolymer, comprising:

[0040] Under the action of a catalyst, the compound of formula (2), the compound of formula (3) and the compound of formula (4) are reacted in a solvent to obtain a polymer including a structural unit of formula (5);

[0041] The polymer and methyl iodide are subjected to a quaternization reaction in a polar solvent to obtain a polymer comprising a structural unit of formula (1);

[0042]

[0043] In formula (3), 0≤n≤14, n is preferably 0-12, more preferably 4-10, more preferably 8-10, and most preferably 10; in the present invention, it is preferred to use long-chain alkylfluorene monomers, especially dodecylfluorene monomers, so that the prepared hyperbranched copolymer and the obtained film have better effects.

[0044] The terminal group in formula (4) is a methyl group;

[0045] In formula (5), 0<x≤0.1, x is preferably 0.01-0.08, more preferably 0.01-0.05, more preferably 0.02-0.04, and most preferably 0.03; 0≤n≤14, n is preferably 0-12, more preferably 4-10, more preferably 8-10, and most preferably 10.

[0046] In the present invention, the catalyst is preferably a superacid catalyst, more preferably one or more mixtures selected from trifluoromethanesulfonic acid, methanesulfonic acid and Eaton's reagent.

[0047] In the present invention, the catalyst is preferably added under low temperature conditions; the low temperature is preferably -40 to 10°C, more preferably -30 to 5°C, more preferably -20 to 0°C, more preferably -10 to 0°C, and most preferably 0°C.

[0048] In the present invention, the compound of formula (2) is p-terphenyl, the compound of formula (3) is a fluorene monomer, and the compound of formula (4) is N-methylpiperidone.

[0049] The present invention has no particular limitation on the source of the compound of formula (3), which can be prepared by methods well known to those skilled in the art.

[0050] In the present invention, the molar ratio of the compound of formula (2), the compound of formula (4) and the compound of formula (3) is preferably (0.9-1.0):(1.0-1.1):(0-0.1), and more preferably 0.95:1.05:0.05.

[0051] In the present invention, the molar ratio of the catalyst to the substrate ketone (N-methylpiperidone) is preferably 1:(10.5-12.0), and more preferably 1:(11-11.5).

[0052] In the present invention, the solvent is preferably an aprotic solvent, more preferably one or more selected from dichloromethane and chloroform. In the present invention, the volume ratio of the catalyst to the solvent is preferably 1: (1.0-2.0), more preferably 1: 1.5. In the present invention, the solid content of the raw material in the solvent is preferably 20-30%, more preferably 25%.

[0053] In the present invention, the reaction process preferably further comprises: adding trifluoroacetic acid; the mass ratio of the catalyst to trifluoroacetic acid is preferably 10.0:(1.0-1.5), more preferably 10:(1.2-1.4), and most preferably 10:1.3.

[0054] In the present invention, the reaction is preferably carried out under magnetic stirring; the reaction temperature is preferably room temperature, more preferably 20-30°C, most preferably 25°C; the reaction time is preferably 2-6 hours, more preferably 3-5 hours, most preferably 4 hours.

[0055] In the present invention, after the reaction is completed, it is preferred that the following steps are further included:

[0056] The obtained reaction product was poured into ethanol to precipitate a polymer.

[0057] In the present invention, the precipitated polymer preferably further comprises water washing and vacuum drying to obtain the polymer.

[0058] In the present invention, the polar solvent is preferably selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.

[0059] In the present invention, the molar ratio of the polymer to methyl iodide is preferably (1.0-1.1): (1.2-1.5), more preferably 1.05: (1.3-1.4). In the present invention, the ratio of the polymer to the polar solvent is preferably (1.0-1.1) g: (10-15) mL, more preferably 1.05 g: (11-14) mL, and most preferably 1.05 g: (12-13) mL.

[0060] In the present invention, the quaternization reaction process preferably further includes adding potassium carbonate, and the potassium carbonate is preferably anhydrous potassium carbonate; the molar ratio of the potassium carbonate to methyl iodide is preferably 1.0:(1.0-1.2).

[0061] In the present invention, the quaternization reaction is preferably carried out under the condition of magnetic stirring; the temperature of the quaternization reaction is preferably room temperature, more preferably 20 to 30° C., and most preferably 25° C.; the time of the quaternization reaction is preferably 20 to 30 hours, more preferably 22 to 28 hours, and most preferably 24 hours.

[0062] In the present invention, after the quaternization reaction is completed, it is preferred that the following steps are further included:

[0063] The obtained reaction product was poured into ethyl acetate for precipitation to obtain a hyperbranched copolymer.

[0064] In the present invention, the precipitation preferably further includes water washing and vacuum drying to obtain a hyperbranched copolymer.

[0065] In the present invention, the preparation method of the hyperbranched copolymer preferably comprises:

[0066] The compound of formula (2), the compound of formula (3) and the compound of formula (4) are simultaneously added into a pressure-resistant bottle containing a non-protonic solvent, and a superacid as a catalyst and a small amount of trifluoroacetic acid are added at low temperature, wherein the solid content is 20-30%; the mixture is reacted at room temperature for 2-6 hours with magnetic stirring to obtain a viscous polymer solution containing formula (5), and the product is poured into ethanol to precipitate the polymer; the polymer of formula (5) is then dissolved in a polar solvent, anhydrous potassium carbonate and iodomethane are added to quaternize it, and the mixture is reacted at room temperature for 24 hours with magnetic stirring to obtain a viscous polymer solution containing formula (1), and the product is poured into ethyl acetate to precipitate the polymer.

[0067] In the present invention, the branched structure is a type of highly branched three-dimensional macromolecule, the branched polymer has many branching points, the molecular chain is not easy to entangle, and the obtained polymer has a high molecular weight. In the present invention, the self-supporting film is a film prepared by casting or other processes, and no base film or other supporting materials are used in the process.

[0068] The present invention provides a film, which is prepared from the hyperbranched copolymer described in the above technical solution or the hyperbranched copolymer prepared by the method described in the above technical solution.

[0069] In the present invention, the film is preferably selected from a polyelectrolyte membrane or an anion exchange membrane; the thickness of the film is preferably ≤10 microns, more preferably 6 to 9 microns, and most preferably 8 microns.

[0070] The present invention provides a polyelectrolyte membrane, which is prepared from the hyperbranched copolymer described in the above technical solution or the hyperbranched copolymer prepared by the method described in the above technical solution.

[0071] In the present invention, the method for preparing the polyelectrolyte membrane preferably comprises:

[0072] The hyperbranched copolymer is dissolved in a solvent, and then a film is formed by a casting method, and then dried.

[0073] In the present invention, the solvent is preferably dimethyl sulfoxide; the solid content of the solvent after being dissolved in the solvent is preferably 3-7wt%, more preferably 4-6wt%, and most preferably 5wt%; during the film-casting process, the copolymer solution is preferably poured onto a glass plate to allow it to spread naturally; the drying temperature is preferably 70-90°C, more preferably 75-85°C, and most preferably 80°C; the drying time is preferably 4-8 hours, more preferably 5-7 hours, and most preferably 6 hours.

[0074] The present invention provides an anion exchange membrane, which is prepared from the polyelectrolyte membrane described in the above technical solution.

[0075] In the present invention, the method for preparing the anion exchange membrane preferably comprises:

[0076] The polyelectrolyte membrane is exchanged in a sodium hydroxide solution to obtain an anion exchange membrane.

[0077] In the present invention, the concentration of the sodium hydroxide solution is preferably 0.5-1.5 mol / L, more preferably 0.8-1.2 mol / L, and most preferably 1 mol / L; the exchange temperature is preferably 50-70°C, more preferably 55-65°C, and most preferably 60°C; the exchange time is preferably 10-15 hours, more preferably 12 hours.

[0078] The high ion exchange capacity of polymethylpiperidinium-(tri)biphenyl polymers leads to high water absorption and high swelling rate of ion membranes, which is not conducive to the dimensional stability of the membranes; the thickness of commonly used anion exchange membranes is usually above 20 microns, which is a great challenge for the preparation of ultra-thin films (less than 10 microns). The present invention develops a new type of branched monomer and prepares a hyperbranched anion exchange membrane through superacid polymerization, which can inhibit the membrane from excessive swelling and retain appropriate mechanical properties while also obtaining an ultra-thin ion membrane.

[0079] Example 1

[0080] 2.24 g (9.8 mmol) of p-terphenyl, 1.14 g (10.1 mmol) of N-methylpiperidone and 83.4 mg (0.25 mmol) of dodecylfluorenyl monomer (1-bromododecane is reacted with magnesium powder to prepare a Grignard reagent, which is then reacted with 9-fluorenone for 2 to 3 hours. The obtained product is reacted with hydrochloric acid and then purified by column chromatography to obtain a product having the structure of formula (3) (n is 10), and the preparation method is shown in Example 6), 10 mL of dichloromethane and 1 mL of trifluoroacetic acid are added to dissolve the product, and the temperature of the reaction system is lowered to 0° C. Then 9 mL of trifluoromethanesulfonic acid is quickly poured into the pressure bottle, and the reaction temperature is maintained at about 0° C. for 3 hours; the reaction system is poured into ethanol to precipitate a polymer solid; after washing with water and vacuum drying, a branched copolymer PPTDF-2.5 is obtained;

[0081] 3.03 g of the obtained polymer PPTDF-2.5 was dissolved in 100 mL of dimethyl sulfoxide, and 1.26 g (9.1 mmol) of anhydrous potassium carbonate and 3.5 mL of iodomethane solution were added and reacted for 24 hours; the obtained polymer solution was poured into ethyl acetate to precipitate the polymer solid, which was washed with water and vacuum dried to obtain the quaternized branched copolymer PPTDF-QA-2.5, and the reaction scheme thereof is as follows:

[0082]

[0083] The NMR characterization of the product prepared in Example 1 is as follows Figure 2 As shown by Figure 2 It can be seen that the H NMR spectrum shows that the H signals of the methyl (Hg) and methylene (Hf) groups connected to the nitrogen atom on the piperidine cation in the polymer appear at 3.15 ppm and 3.38 ppm, respectively, and the integrated area ratio is 4.06:6.00, which is close to the theoretical value (4:6), indicating that the polymer is completely quaternized.

[0084] Example 2

[0085] 2.25 g (9.8 mmol) of p-terphenyl, 1.14 g (10.1 mmol) of N-methylpiperidone and 61.7 mg (0.25 mmol) of hexaalkylfluorenyl monomer (1-bromohexane is reacted with magnesium powder to prepare a Grignard reagent, which is then reacted with 9-fluorenone for 2 to 3 hours. The obtained product is reacted with hydrochloric acid and then further purified by column chromatography to obtain a product having the structure of formula (3) (n is 4), and the preparation method is shown in Example 6), 10 mL of dichloromethane and 1 mL of trifluoroacetic acid are added to dissolve the product, and the temperature of the reaction system is lowered to 0° C.; 9 mL of trifluoromethanesulfonic acid is then quickly poured into the pressure bottle, and the reaction temperature is maintained at about 0° C. for 3 hours; the reaction system is poured into ethanol to precipitate a polymer solid, which is washed with water and dried in vacuo to obtain a branched copolymer PPTHF-2.5.

[0086] 3.01 g of the obtained polymer PPTHF-2.5 was dissolved in 100 mL of dimethyl sulfoxide, and 1.26 g (9.1 mmol) of anhydrous potassium carbonate and 3.5 mL of iodomethane solution were added and reacted for 24 hours; the obtained polymer solution was poured into ethyl acetate to precipitate the polymer solid, which was washed with water and vacuum dried to obtain a quaternized branched copolymer PPTHF-QA-2.5, and the reaction route is as follows:

[0087]

[0088] Example 3

[0089] 2.24 g (9.8 mmol) of p-terphenyl, 1.14 g (10.1 mmol) of N-methylpiperidone and 48.1 mg (0.25 mmol) of ethylfluorenyl monomer (ethyl bromide is reacted with magnesium powder to prepare a Grignard reagent, which is then reacted with 9-fluorenone for 2 to 3 hours. The obtained product is reacted with hydrochloric acid and further purified by column chromatography to obtain a product having the structure of formula (3) (n is 0), and the preparation method is shown in Example 6), 10 mL of dichloromethane and 1 mL of trifluoroacetic acid are added to dissolve the product, and the temperature of the reaction system is lowered to 0°C; 9 mL of trifluoromethanesulfonic acid is then quickly poured into the pressure bottle, and the reaction temperature is maintained at about 0°C for 3 hours; the reaction system is poured into ethanol to precipitate a polymer solid, which is washed with water and dried in vacuo to obtain a branched copolymer PPTEF-2.5.

[0090] 3.00 g of the obtained polymer PPTDF-2.5 was dissolved in 100 mL of dimethyl sulfoxide, and 1.26 g (9.1 mmol) of anhydrous potassium carbonate and 3.5 mL of iodomethane solution were added and reacted for 24 hours; the obtained polymer solution was poured into ethyl acetate to precipitate the polymer solid, which was washed with water and vacuum dried to obtain the quaternized branched copolymer PPTEF-QA-2.5, and the reaction route is as follows:

[0091]

[0092] Example 4

[0093] 2.24 g (9.8 mmol) of p-terphenyl, 1.14 g (10.1 mmol) of N-methylpiperidone and 33.1 mg (0.10 mmol) of dodecylfluorenyl monomer (structure of formula (3), n is 10) were added to a dry pressure bottle, 10 mL of dichloromethane and 1 mL of trifluoroacetic acid were added to dissolve, and the temperature of the reaction system was lowered to 0°C; 9 mL of trifluoromethanesulfonic acid was then quickly poured into the pressure bottle, and the reaction temperature was maintained at about 0°C for 3 hours; the reaction system was poured into ethanol to precipitate a polymer solid, which was washed with water and vacuum dried to obtain a branched copolymer PPTDF-1.

[0094] The obtained polymer 3.03 g PPTDF-1 was dissolved in 100 mL dimethyl sulfoxide, and 1.26 g (9.1 mmol) of anhydrous potassium carbonate and 3.5 mL of iodomethane solution were added and reacted for 24 hours; the obtained polymer solution was poured into ethyl acetate to precipitate the polymer solid, which was washed with water and vacuum dried to obtain the quaternized branched copolymer PPTDF-QA-1.

[0095] Example 5

[0096] Add 2.24g (9.8mmol) of p-terphenyl, 1.14g (10.1mmol) of N-methylpiperidone and 0.17g (0.51mmol) of dodecylfluorene monomer (structure of formula (3), n is 10) to a dry pressure bottle, add 10mL of dichloromethane and 1mL of trifluoroacetic acid to dissolve, and then lower the temperature of the reaction system to 0°C. Then quickly pour 9mL of trifluoromethanesulfonic acid into the pressure bottle, maintain the reaction temperature at around 0°C and react for 3 hours. Pour the reaction system into ethanol to precipitate the polymer solid. After washing with water and vacuum drying, the branched copolymer PPTDF-5 is obtained. Take the obtained polymer 3.00g PPTDF-5 and dissolve it in 100mL of dimethyl sulfoxide, add 1.26g (9.1mmol) of anhydrous potassium carbonate and 3.5mL of iodomethane solution and react for 24 hours. The obtained polymer solution was poured into ethyl acetate to precipitate the polymer solid, which was then washed with water and vacuum dried to obtain the quaternized branched copolymer PPTDF-QA-5.

[0097] Example 6

[0098] The Grignard reagent was prepared by reacting 1-bromododecane with magnesium powder and dissolved in anhydrous tetrahydrofuran to prepare a 1 mol / L solution. 9-Fluorenone (9.0 g) was completely dissolved in 150 mL of dry tetrahydrofuran under continuous nitrogen. Then, the above Grignard reagent (1 mol / L, 60 mL) was placed in a dropping funnel and slowly dripped into the solution. The reaction temperature was controlled at 20°C. After dripping, the reaction was quenched with a saturated aqueous solution of ammonium chloride. The oil phase was dried with magnesium sulfate and the solvent was removed in vacuo. Finally, a yellow solid (14.6 g, yield 83.4%) was obtained after purification by column chromatography (n-hexane: ethyl acetate = 10: 1). The above monomer (3.4 g) was then dissolved in 100 mL of dichloromethane containing 1.3 mL of acetic acid. Then, an excess of hydrochloric acid (12 mol / L, 10 mL) was added dropwise under continuous stirring at room temperature. After the addition, the solution was heated to 60°C. The reaction solution was neutralized with sodium bicarbonate, and then the oil phase was separated and further purified by column chromatography (n-hexane: dichloromethane = 20: 1) to obtain the final product, dodecylfluorene monomer, a white solid (2.7 g, yield 81.8%). 1H NMR (500MHz, CDCl3, ppm) δ7.99-7.61 (m, 4H), 7.46-7.24 (m, 4H), 6.78 (t, 1H), 2.87 (m, 2H), 1.71 (m, 2H), 1.55-1.20 (m, 16H), 0.90 (t, 3H). 13 C NMR (125 MHz, CDCl3, ppm) δ 140.85, 139.50, 138.62, 137.66, 135.39, 131.40, 127.65, 127.36, 126.93, 126.88, 125.01, 119.85, 119.72, 119.53, 32.05, 29.80, 29.78, 29.73, 29.68, 29.50, 22.83, 14.26 (as Figure 6 shown).

[0099] By changing the type of Grignard reagent, the other two alkylfluorene monomers were prepared. The reaction conditions were in accordance with the above experimental conditions. The NMR spectra confirmed the structures of the compounds:

[0100] Hexylfluorene monomer: 1 H NMR (500MHz, CDCl3, ppm) δ7.94 (d, 1H), 7.83 (d, 3H), 7.78-7.72 (m, 2H), 7.45- 7.32 (m, 4H), 6.81 (t, 1H), 2.91 (m, 2H), 1.76 (m, 1H), 1.50 (m, 4H), 1.01 (t, 3H). 13 CNMR (125MHz, CDCl3, ppm)δ140.83, 139.48, 138.59, 137.64, 135.37, 131.39, 127.64, 127.35, 126.92, 129.87, 124.98, 119.83, 119.70, 119.51, 31.86, 29.80, 29.42, 22.79, 14.16, (such as Figure 7 shown);

[0101] Ethylfluorene monomer: 1 H NMR (500MHz, CDCl3, ppm) δ7.97 (d, 1H), 7.84-7.76 (dd, 2H), 7.72 (d, 3H), 7.46-7.33 (m, 4H), 6.92 (m, 1H, 2.46 (d, 3H). 13C NMR (125 MHz, CDCl3, ppm) δ 140.80, 139.41, 138.58, 137.78, 136.59, 134.84, 127.66, 127.38, 126.94, 125.11, 124.97, 119.86, 119.67, 119.54, 15.40 (as Figure 8 shown).

[0102] Comparative Example 1

[0103] 2.24 g (9.8 mmol) of p-terphenyl, 1.14 g (10.1 mmol) of N-methylpiperidone and 0.17 g (0.51 mmol) of dodecylfluorenyl monomer (structure of formula (3), n is 10) were added to a dry pressure bottle, 10 mL of dichloromethane and 1 mL of trifluoroacetic acid were added to dissolve, and the temperature of the reaction system was lowered to 0°C. Then 9 mL of trifluoromethanesulfonic acid was quickly poured into the pressure bottle, and the reaction temperature was maintained at around 0°C for 6 hours. The reaction system was poured into ethanol to precipitate a polymer solid, which was washed with water and dried in vacuo to obtain a branched copolymer PPTDF-5.

[0104] The polymer prepared in Comparative Example 1 was difficult to continue to dissolve in dimethyl sulfoxide and was in a gel state.

[0105] Comparative Example 2

[0106] 2.30 g (10.0 mmol) of p-terphenyl and 1.14 g (10.1 mmol) of N-methylpiperidone were added to a dry pressure bottle, and 10 mL of dichloromethane and 1 mL of trifluoroacetic acid were added to dissolve the mixture. The temperature of the reaction system was then lowered to 0°C. 9 mL of trifluoromethanesulfonic acid was then quickly poured into the pressure bottle. The reaction temperature was maintained at around 0°C for 12 hours. The reaction system was poured into ethanol to precipitate a polymer solid, which was then washed with water and dried in vacuo to obtain a branched copolymer PPT.

[0107] 3.01 g of the obtained polymer PPT was dissolved in 100 mL of dimethyl sulfoxide, and 1.26 g (9.1 mmol) of anhydrous potassium carbonate and 3.5 mL of iodomethane solution were added and reacted for 24 hours; the obtained polymer solution was poured into ethyl acetate to precipitate the polymer solid, which was washed with water and vacuum dried to obtain the quaternized branched copolymer PPT-QA.

[0108] Comparative Example 3

[0109] 2.24 g (9.8 mmol) of p-terphenyl, 1.14 g (10.1 mmol) of N-methylpiperidone and 30.7 mg (0.10 mmol) of 1,3,5-triphenylbenzene (purchased from Inokai Reagent Co., Ltd.) were added to a dry pressure bottle, and 10 mL of dichloromethane and 1 mL of trifluoroacetic acid were added to dissolve the mixture, and the temperature of the reaction system was lowered to 0°C. 9 mL of trifluoromethanesulfonic acid was then quickly poured into the pressure bottle, and the reaction temperature was maintained at around 0°C for 3 hours. The reaction system was poured into ethanol to precipitate a polymer solid, which was washed with water and dried in vacuo to obtain a branched copolymer PPTTB-1.

[0110] 3.00 g of the obtained polymer PPTTB-1 was dissolved in 100 mL of dimethyl sulfoxide, and 1.26 g (9.1 mmol) of anhydrous potassium carbonate and 3.5 mL of iodomethane solution were added and reacted for 24 hours; the obtained polymer solution was poured into ethyl acetate to precipitate the polymer solid, which was washed with water and vacuum dried to obtain the quaternized branched copolymer PPTTB-QA-1.

[0111] Comparative Example 4

[0112] 2.24 g (9.8 mmol) of p-terphenyl, 1.14 g (10.1 mmol) of N-methylpiperidone and 76.6 mg (0.25 mmol) of 1,3,5-triphenylbenzene (purchased from Inokai Reagent Co., Ltd.) were added to a dry pressure bottle, and 10 mL of dichloromethane and 1 mL of trifluoroacetic acid were added to dissolve the mixture, and the temperature of the reaction system was lowered to 0°C. 9 mL of trifluoromethanesulfonic acid was then quickly poured into the pressure bottle, and the reaction temperature was maintained at around 0°C for 3 hours. The reaction system was poured into ethanol to precipitate a polymer solid, which was washed with water and dried in vacuo to obtain a branched copolymer PPTTB-2.5.

[0113] The obtained polymer 3.02g PPTTB-2.5 was dissolved in 100mL dimethyl sulfoxide, and 1.26g (9.1mmol) anhydrous potassium carbonate and 3.5mL iodomethane solution were added and reacted for 24 hours; the obtained polymer solution was poured into ethyl acetate to precipitate the polymer solid, which was washed with water and vacuum dried to obtain the quaternized branched copolymer PPTTB-QA-2.5.

[0114] Comparative Example 5

[0115] 2.24 g (9.8 mmol) of p-terphenyl, 1.14 g (10.1 mmol) of N-methylpiperidone and 0.15 g (0.50 mmol) of 1,3,5-triphenylbenzene (purchased from Inokai Reagent Co., Ltd.) were added to a dry pressure bottle, and 10 mL of dichloromethane and 1 mL of trifluoroacetic acid were added to dissolve the mixture, and the temperature of the reaction system was lowered to 0°C. 9 mL of trifluoromethanesulfonic acid was then quickly poured into the pressure bottle, and the reaction temperature was maintained at around 0°C for 3 hours. The reaction system was poured into ethanol to precipitate a polymer solid, which was washed with water and dried in vacuo to obtain a branched copolymer PPTTB-5.

[0116] 3.00 g of the obtained polymer PPTTB-5 was dissolved in 100 mL of dimethyl sulfoxide, and 1.26 g (9.1 mmol) of anhydrous potassium carbonate and 3.5 mL of iodomethane solution were added and reacted for 24 hours; the obtained polymer solution was poured into ethyl acetate to precipitate the polymer solid, which was washed with water and vacuum dried to obtain the quaternized branched copolymer PPTTB-QA-5.

[0117] Application Example 1

[0118] The polymers prepared in the embodiment and the comparative example were respectively dissolved in dimethyl sulfoxide, the solid content was controlled at 5wt%, and the film was laid by the casting method. The polymer solution was poured on a glass plate and allowed to flow naturally. After drying in an oven at 80°C for 6 hours, a polyelectrolyte membrane (thickness of 30 μm) was obtained; and the counter ion OH was exchanged in a 1 mol / L sodium hydroxide solution at 60°C for 12 hours to obtain - anion exchange membrane.

[0119] Performance Testing

[0120] The water absorption, swelling rate and conductivity of the films obtained from the branched polymers and linear polymers prepared in the examples of the present invention and the comparative examples were tested, and the testing method was as follows:

[0121] The samples were immersed in deionized water at different temperatures for 6 hours, and the excess water on the surface was removed. The water absorption weight (m w ) and length (l w ); Next, the wet film was dried in vacuum at 80 °C for 12 h, and the dry weight (m d ) and length (l d ); The water absorption rate and swelling rate of the membrane are calculated according to the following formula:

[0122] Water absorption rate = [(m w -m d ) / m d ]×100%

[0123] Swelling ratio = [(l w -l d) / l d ]×100%.

[0124] The hydroxide conductivity of the membrane was determined using a four-point probe AC ​​impedance method on an electrochemical workstation (BioLogic VSP); during the test, the membrane was immersed in an alkaline solution for 48 hours at room temperature to complete ion exchange and then cut into a size of 1×4 cm; after removing carbon dioxide with nitrogen in a glove box, the sample was measured for resistance in ultrapure water at a temperature range of 30°C to 80°C; the conductivity was determined by the following formula:

[0125] Conductivity = l / (twR)

[0126] Where l is the length between the electrodes, t and w are the thickness and width of the film being measured, respectively, and R represents the impedance.

[0127] The test results are shown in Tables 1 to 3.

[0128] Table 1 Swelling rate of polyelectrolyte membrane in water at different temperatures

[0129]

[0130] Table 2 Water absorption of polyelectrolyte membrane in water at different temperatures

[0131]

[0132]

[0133] Table 3 Conductivity of polyelectrolyte membrane in water at different temperatures

[0134]

[0135] It can be seen that the effect of introducing branched monomers is significantly improved. With the increase of branched monomer content, the phase separation behavior of the membrane is more obvious and the mechanical properties are also improved. Figure 1 As shown, according to the small angle scattering (SAXS) test, the size of the ion cluster increases, and the peak intensity of the microphase separation region also gradually increases. The mechanical properties are tested as follows: The tensile test is performed by INSTRON-1121 at room temperature at a rate of 5 mm / min. Before the test, the sample is made into a dumbbell shape (1×4 cm).

[0136] The H2 / O2 single cell performance of the anion exchange membrane obtained from the polymer of Example 1 was tested by placing the prepared membrane electrode in a cell fixture and testing the single cell performance at 80°C; the test results are shown in Table 4.

[0137] Table 4 H2 / O2 single cell performance of PPTDF-QA-2.5 anion exchange membrane

[0138]

[0139] like Figure 3 to Figure 5 As shown, by comparing Example 1, Example 2 and Example 3, for the introduction of short alkyl branched monomers, the obtained branched electrolyte membrane is brittle and difficult to achieve ultra-thin thickness. The branched polyelectrolyte membrane introduced with long alkyl (n=10) has higher strength and is conducive to the preparation of ultra-thin films, and its battery power density is also improved.

[0140] As shown in Table 5, comparing Example 1 with Comparative Examples 2 to 5, the polyelectrolyte membrane prepared using 1,3,5-triphenylbenzene as a branching monomer as reported so far has a thickness of 20 to 40 microns, and it is difficult to obtain an ultra-thin film less than 10 microns; whereas the use of dodecylfluorene-based monomers can prepare an anion exchange membrane less than 10 microns with excellent mechanical strength.

[0141] Table 5 Thickness comparison of PPT-QA anion exchange membrane

[0142]

[0143] The comonomer used in the prior art is a polyaromatic ring compound (quaterphenyl), which is used in large amounts and has a high cost; a substrate is used to enhance the mechanical strength of the membrane, and the membrane is not self-supporting. The present invention designs a novel hyperbranched polyelectrolyte membrane. This polymer is obtained by superacid catalysis, and a small amount of branched monomers are introduced to obtain an anion exchange membrane with excellent mechanical properties, with small amounts and low costs. The water swelling rate of the structure provided by the present invention is effectively suppressed, and due to the introduction of long alkyl groups, a more obvious phase separation microphase structure is effectively formed. At the same time, due to its high strength and high flexibility, a self-supporting ion membrane with a thickness of 8 microns can be obtained. The branched monomer provided by the present invention can be used to prepare a hyperbranched ionic polymer. The branched structure of the polymer can suppress the water swelling of the ion membrane, and the use of the structure can obtain an ultra-thin ion exchange membrane.

[0144] Although the present invention has been described and illustrated with reference to specific embodiments of the present invention, these descriptions and illustrations do not limit the present invention. It will be clearly understood by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention as defined by the appended claims, so that specific circumstances, materials, material compositions, materials, methods or processes are suitable for the goals, spirit and scope of the present application. All such modifications are intended to be within the scope of the appended claims. Although the methods disclosed herein have been described with reference to specific operations performed in a specific order, it should be understood that these operations may be combined, subdivided or reordered to form equivalent methods without departing from the teachings of the present invention. Therefore, unless specifically indicated herein, the order and grouping of operations are not limitations of the present application.

Claims

1. A hyperbranched copolymer comprising a structural unit represented by formula (1): In formula (1), 0<x≤0.1, 0≤n≤14.

2. A method for preparing a hyperbranched copolymer, comprising: Under the action of a catalyst, the compound of formula (2), the compound of formula (3) and the compound of formula (4) are reacted in a solvent to obtain a polymer including a structural unit of formula (5); The polymer and methyl iodide are subjected to a quaternization reaction in a polar solvent to obtain a polymer comprising a structural unit of formula (1); In formula (3), 0≤n≤14, The terminal group in formula (4) is a methyl group; In formula (5), 0<x≤0.1, 0≤n≤14.

3. The method according to claim 2, characterized in that The catalyst is an acidic catalyst selected from one or more of trifluoromethanesulfonic acid, methanesulfonic acid and Eaton's reagent.

4. The method according to claim 2, characterized in that: The catalyst is added under low temperature conditions, and the low temperature is -40 to 10°C.

5. The method according to claim 2, characterized in that: The molar ratio of the compound of formula (2), the compound of formula (4) and the compound of formula (3) is (0.9-1.0):(1.0-1.1):(0-0.1).

6. The method according to claim 2, characterized in that The solvent is an aprotic solvent selected from one or more of dichloromethane and chloroform.

7. The method according to claim 2, characterized in that The volume ratio of the catalyst to the solvent is 1:(1.0-2.0).

8. The method according to claim 2, characterized in that: The polar solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.

9. The method according to claim 2, characterized in that: The temperature of the reaction and the quaternization reaction is independently selected from room temperature; The reaction time is 2 to 6 hours; The quaternization reaction time is 20 to 30 hours.

10. A film prepared from the hyperbranched copolymer according to claim 1 or the hyperbranched copolymer prepared by the method according to claim 2.

Citation Information

Patent Citations

  • Quaternized cross-linked polymer, anion exchange membrane and preparation and application methods of quaternized cross-linked polymer and anion exchange membrane

    CN113831540A

  • Hyperbranched imidazole copolymer as well as preparation method and application thereof

    CN115044017A